Training and Mentoring: Improving Pedagogical Competence of Catholic Religious Education Teachers - Din Oloan Sihotang; Johannes Sohirimon Lumbanbatu; Ermina waruwu; Mariana Siregar; Fransiskus Tarigan (Universitas Muhammadiyah Palembang, 2023)
Improving the pedagogical competence of Catholic Religious Education teachers in Karo District's elementary schools is typically carried out through Teacher Working Groups (KKG) or workshops. Workshops for teachers usually focus on developing instructional materials. The implementation of Community Service (PkM) aims to enhance the pedagogical competence of teachers in planning and conducting lessons, organizing educational teaching methods, and utilizing information technology in teaching. The PkM activities consist of a two-day training session followed by two months of mentoring. The results show a significant improvement in the indicators of teachers' pedagogical competence, while partner satisfaction evaluations reflect the positive impact of these activities. It is expected that the Director General of Catholic Religious Affairs will ensure that each teacher competency improvement program includes concrete steps and a continuous monitoring and evaluation system to ensure the effective sustainability of pedagogical competence enhancement.